Psychological Stress, Gut–Brain Axis Dysfunction, and Inflammatory Biomarkers in Patients with Irritable Bowel Syndrome: A Cross-Sectional Clinical Study - Syed Muhammad Omer, Benazir Javed, Nasir Ali, Aysha Rashid, Aliza Raheel, Nughza Zaheer (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Irritable bowel syndrome (IBS) is increasingly viewed as a disorder of gut–gut-gut-brain-immune interaction in which psychological stress, low-grade inflammation, and epithelial-barrier failure converge. Evidence from South-Asian populations, however, remains sparse. Objective: To examine whether perceived stress parallels systemic inflammatory activity and zonulin-defined permeability in Pakistani IBS patients, and whether these biological indices explain symptom severity. Methods: In a cross-sectional study at DHQ Teaching Hospital, Narowal (May 2022 – May 2023), eighty Rome-IV IBS patients and sixty age- and sex-matched healthy controls were enrolled. Demography, body mass index, and disease duration were recorded. The Perceived Stress Scale-10 (PSS-10) quantified psychological load; the IBS Severity Scoring System (IBS-SSS) assessed clinical burden. Serum high-sensitivity C-reactive protein (CRP), interleukin-6 (IL-6), tumour-necrosis-factor-α (TNF-α), and zonulin were measured by ELISA. Welch t tests compared groups; multivariable linear regression evaluated predictors of IBS-SSS. Results: Compared with controls, patients exhibited significantly higher stress (23.2 ± 5.6 vs 15.0 ± 4.0), CRP (4.35 ± 1.17 vs 2.10 ± 0.71 mg L⁻¹), IL-6 (12.42 ± 3.15 vs 7.19 ± 2.05 pg mL⁻¹), TNF-α (19.01 ± 3.81 vs 12.54 ± 2.51 pg mL⁻¹) and zonulin (46.72 ± 8.50 vs 29.93 ± 6.01 ng mL⁻¹) (all p < 0.0001). Nevertheless, stress and biomarker levels together explained only 3 % of IBS-SSS variance (R² = 0.034, p = 0.62). Conclusion: IBS in this Pakistani cohort is characterised by a triad of psychological distress, systemic inflammation, and intestinal permeability, yet contemporaneous stress and cytokine concentrations do not linearly dictate symptom severity. Longitudinal, multi-omic studies are needed to delineate temporal dynamics and to personalise gut–gut-brain-immune-targeted therapies in South-Asian IBS. Keywords: Irritable bowel syndrome; Psychological stress; Gut–brain axis; Low-grade inflammation; Zonulin; Pakistan